Institutional Barriers and Strategic Enablers: A Knowledge Management Scale Development Study in Indonesian Higher Education - Risana Rachmatan; Muhammad Syamsul Maarif; Muhammad Adam; Hizir Sofyan (Heca Sentra Analitika, 2026)
Knowledge management (KM) is increasingly important for Indonesian universities, which face rapid technological change and heightened demands for transparency, quality, and competitiveness. This study developed and validated a measurement instrument to identify key barriers and enablers of KM implementation in Indonesian higher education. A 22-item scale was developed for the local context and organized into six aspects: trust in individuals, trust in management, reward system, organizational process, IT, and technical support. The scale was produced in two versions: one for lecturers/education staff and one for students. Content validity was evaluated using the Content Validity Ratio (CVR) and the Content Validity Index (CVI) with expert panels (eight raters), followed by a pilot administration to 60 respondents (30 lecturers/staff and 30 students). The scale demonstrated strong content validity (mean I-CVI 0.87–0.91), acceptable item discrimination (lecturer/staff: 0.471–0.834; student: 0.250–0.785), and high internal consistency (Cronbach’s alpha: 0.952 for lecturer/staff; 0.923 for students). These results indicate that the instrument is robust for diagnosing KM enablers and barriers in Indonesian universities and can support targeted policies and interventions. Future studies should expand validation across diverse institutions nationwide.